KONTRIBUSI POWER OTOT TUNGKAI DAN KOORDINASI MATA DAN KAKI TERHADAP KECEPATAN TENDANGAN SABIT SISWA EKSTRAKURIKULER PENCAK SILAT SMK NEGERI 7 PEKANBARU - Nicco Alcin Prablly; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on observation or direct observations on Student extracurricular pencak silat SMKN 7 Pekanbaru, Researchers En countered some concerns regarding the ability of the crescent kick as follows: when students perform crescent kick, students do not yet optimal. This was seen at the time of kicking, rarely on target, kicks are not so powerful that rarely makes the opponent fall and kicks are easily caught so often receive a beating from the opponent, to the detriment of the fighters it self , The problem is apparently due contribution limb muscle power and foot-eye coordination to speed crescent kick. The purpose of this study to determine how much contribution limb muscle power and coordination of the eyes and feet together to speed crescent kick . The population in this study is the whole Student Extracurricular Pencak Silat SMKN 7 Pekanbaru totaling 12 people. The technique of collecting data was total sampling because the population was not the big amount. Thus the study sample as many as 12 people. The research instrument used Standing board Jump test to know the results of the Power Muscle leg, and foot-eye coordination tests using Soccer Wall Volley Test. The crescent kick speed test to find out the result / score of Speed The crescent kick within 10 seconds. . The data were analysed by using Product Moment Correlation and the contribution was analysed by using determinant coefficient. Based on the research results can be drawn the following conclusions: Contribution given limb muscle power with a crescent kick velocity is equal to 1,46%. The Contributions made eye coordination and foot crescent kick to the speed that is equal to 0.83%. The Contributions given Power muscular limbs and eye coordination and foot speed kick the crescent is equal to 2.4%. while 97.6% are influenced by other factors.Key Words: Power of leg muscle, eye and foot coordination, Speed crescent kick.